Treatment With Nilvadipine Mitigates Inflammatory Pathology and Improves Spatial Memory in Aged hTau Mice After Repetitive Mild TBI - Morin, Alexander; Mouzon, Benoit; Ferguson, Scott; Paris, Daniel; Saltiel, Nicole; Lungmus, Carlyn; Mullan, Mike; Crawford, Fiona (Frontiers in Aging Neuroscience, 2018)
Mild TBI (mTBI) is the most common form of brain trauma worldwide. The effects of mTBI are not well-studied within the elderly population, yet older adults constitute a significant portion of all mTBI patients. Few preclinical studies have focused on the effects of mTBI, or mTBI treatments, in the aged brain, and none have explored repetitive mTBI. In this study, we have administered our well-characterized 5-injury repetitive mTBI model (5 r-mTBI) to hTau mice aged 24 months to explore the neurobehavioral and neuropathological outcomes, and the effects of treatment with the dihydropyridine, Nilvadipine. Our previous studies have shown that Nilvadipine inhibits spleen tyrosine kinase, is effective at reducing inflammation, tau hyperphosphorylation and amyloid production, and it has recently been investigated in a European Phase III clinical trial for Alzheimer’s Disease (AD). In our 24-month-old r-mTBI mice, we observed increased neuroinflammation and a trend toward impaired cognitive performance compared to sham controls. Treatment with Nilvadipine mitigated the TBI-induced inflammatory response in aged r-mTBI animals and significantly improved spatial memory. To our knowledge, this is the only preclinical study focusing on the treatment of r-mTBI in the aged, and these results suggest a therapeutic potential of Nilvadipine for consequences of mTBI.